Pattern of potential medication errors in a tertiary care hospital in Nepal. - A, Kadir; P, Subish; K, Anil; B, Ram (Indian Journal of Pharmacy Practice)
In the process of treating a patient errors may occur at any stage of pharmacotherapy starting from the prescription writing, dispensing, administration and monitoring. The present study was conducted to identify the potential medication errors among the outpatients and to categorize them based on the onset, underlying cause, medication error index and severity of medication error. A cross-sectional study was conducted in Manipal Teaching Hospital, Pokhara, Nepal between July 2007 to October 2008. The prescriptions having medication error was photocopied and used as the data source. The encountered medication errors were classified based on their onset, underlying cause, medication error index and severity of medication errors. Altogether 66 medication errors were recorded in 59 prescriptions. Medication errors were noticed more in prescribed medication of male patients and with antird microbial class of drugs. All (100%; n=66) the errors had latent onset. More than 2/3 (68.18% n=45) of errors had rd underlying cause as wrong dose. Similarly, more than 2/3 (72.73%; n=48) of errors were found to be medication error index of 'Category B' which suggests an error occurred, but medication did not reach to the patients and the degree of severity of most of the medication errors (69.70%; n=46) were 'B' on severity scale means clinically significant error which can increase need for patient monitoring. Conclusively, the proper communication between pharmacists and prescribers prevented majority of potential errors which is appreciable and should be continued.
Keywords: Medication Error; Nepal; Outpatients; Pharmacovigilance